2013
DOI: 10.1016/j.fbp.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect power ultrasound assisted pre-osmotic treatments in convective drying of guava slices

Abstract: Application of ultrasound to osmotic dehydration of guava slices via indirect sonication using an ultrasonic bath system and direct sonication using an ultrasonic probe system was studied. Pre-treatments were designed in three osmotic solution concentrations of 0, 35, and 70 °Brix at indirect ultrasonic bath power from 0 to 2.5 kW for immersion times ranging for 20-60 min and direct ultrasonic probe amplitudes from 0 to 35% for immersion times of 6-20 min. The calculated ultrasound intensities from calorimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
86
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 26 publications
12
86
0
8
Order By: Relevance
“…Kek et al (2013) have studied the influence of ultrasound-assisted osmotic pretreatments on the convective drying of guava slices. Their results showed that the ultrasonic pretreated dried samples have presented the lowest vitamin C content due to leaching of solutes to the liquid media promoted by cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…Kek et al (2013) have studied the influence of ultrasound-assisted osmotic pretreatments on the convective drying of guava slices. Their results showed that the ultrasonic pretreated dried samples have presented the lowest vitamin C content due to leaching of solutes to the liquid media promoted by cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…Ponadto suszenie modyfikuje właściwości produktów pochodzenia roślinnego, redukuje ich masę i objętość, co jest korzystne ze względu na ograniczenie kosztów podczas magazynowania i transportu [3,5,14,29].…”
unclassified
“…For indirect sonication of food placed in the ultrasonic water bath, the ultrasound is transferred through water and affects the food immersed in the bath. The ultrasound applied to the bath with food first passes through the walls of the container, therefore its intensity inside the bath is lower than that of the ultrasound source (Feng and Yang, 2010;Kek et al, 2013;Santos et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…When ultrasound is directly applied to a hypertonic solution with immersed samples, and there is no such a barrier as a probe system, strong cavitation near the tip of the probe may generate free radicals being detrimental to foods. The ultrasonic cpe.czasopisma.pan.pl; degruyter.com/view/j/cpe probe can deliver about 100 times much higher of US intensity than an ultrasonic bath (Kek et al, 2013;Santos et al, 2009). For indirect sonication of food placed in the ultrasonic water bath, the ultrasound is transferred through water and affects the food immersed in the bath.…”
Section: Introductionmentioning
confidence: 99%